2006
DOI: 10.1159/000094868
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Is a Better Indicator of Therapeutic Response than C-Reactive Protein within the First Day of Treatment in Pneumonia

Abstract: Acute bacterial infectious diseases are mostly treated empirically at admission before the culture results are available. According to the risk for serious complications in the case of therapeutic failure, it is important to evaluate the therapy results and change to a more appropriate antibiotic regime as soon as possible. In the present study, 40 patients with X-ray-verified community-acquired pneumonia were examined and blood specimens were collected before and within 24 h of treatment. Body temperature, C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…During chronic inflammation, HGF may have the ability to bind to c-Met but be unable to induce cell signalling due to deficient ligation to the co-receptor HSPG. HGF is produced rapidly after injury and ongoing damage, acting as an acute phase protein, and our present data is in agreement with our previous observations that HGF may be a more sensitive marker for monitoring the effect of treatment than CRP [35] (Table 2). Furthermore, knock-out mice lacking the HGF gene do not survive [36], and HGF administration has been used to inhibit and treat several injuries, thus acting as a potent growth factor [10].…”
Section: Discussionsupporting
confidence: 93%
“…During chronic inflammation, HGF may have the ability to bind to c-Met but be unable to induce cell signalling due to deficient ligation to the co-receptor HSPG. HGF is produced rapidly after injury and ongoing damage, acting as an acute phase protein, and our present data is in agreement with our previous observations that HGF may be a more sensitive marker for monitoring the effect of treatment than CRP [35] (Table 2). Furthermore, knock-out mice lacking the HGF gene do not survive [36], and HGF administration has been used to inhibit and treat several injuries, thus acting as a potent growth factor [10].…”
Section: Discussionsupporting
confidence: 93%
“…Our results from the present study show that monitoring of HGF concentrations predicted the effect of anti-biotic treatment in lung infections with high sensitivity. These results are in agreement with our previous observations [14] [15] and show that monitoring HGF during pneumonia might be a reasonable approach to evaluate therapy. Further studies are needed to determine if HGF has a role in the evaluation of empiric antibiotic treatment in infections caused by multiple resistant microorganisms.…”
Section: Parametersupporting
confidence: 93%
“…It was our belief that this property of HGF could be used to predict the efficacy of treatment by monitoring the status of injury, as indicated by changes in HGF concentration. A previous study by us showed that changes in HGF concentration could function as a therapeutic marker in pneumonia [13]- [15]. In the present study, we investigated whether this might apply to other infectious diseases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been shown that HGF is accounted for by malign cell transformation, proliferation, invasion, and metastasis of cancer cells (12,13). It has been reported that HGF levels are increased in sepsis, inflammatory pulmonary diseases, and pneumonia (14,15). Although HGF levels in serum and local fluids have been particularly investigated in acute and chronic inflammatory diseases, there are a limited number of studies on HGF levels and its prognostic value in infectious diseases.…”
Section: Introductionmentioning
confidence: 99%